The Edukasi Gizi Ibu Balita Berbasis Buku KIA Terhadap Pengetahuan dan Status Gizi Kurang - Riana, Asysyifa; Harun, Iriyanti; Irawan, Galuh Chandra; Amalia, Elly (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2024)
SSGI data for 2022 shows that the prevalence of malnourished children under five is 7.7% and in Banten province it has increased from 5.8% to 9.8%. Malnutrition in toddlers is the main cause of growth and development disorders. One of the government programs in dealing with malnourished toddlers is an education class for mothers of toddlers based on MCH books which is expected to be able to improve the nutritional status of malnourished toddlers. This research aims to determine the effect of nutritional education through classes for mothers of toddlers based on MCH books on the nutritional status of malnourished toddlers. Experimental research method with a one group pretest posttest design. The sample for this research was 60 malnourished toddlers using a purposive sampling technique. Primary data includes sample characteristics, maternal nutritional knowledge collected through interviews using questionnaires and anthropometric measurements. Research data was processed using Microsoft Excel and SPSS, analyzed using the Paired Sample T-Test statistical test. The results showed that the majority of toddlers (71.7%) were male, 66.7% of mothers had an elementary school educational background and the majority did not work (76.7%) and came from families with monthly income below the minimum wage. (53.3%). Research data shows that there is a positive change in the mother's nutritional knowledge score, namely 30% to 75% in the good category and 70% to 25% in the poor category. Most toddlers experience an increase in average body weight, body length and z-score value of BB/PB or BB/TB. The results of the Paired Sample T-Test statistical test showed that there was an influence of maternal classroom nutrition education on maternal nutritional knowledge (p=0.000) and nutritional status of toddlers (p=0.000). It is hoped that this class program for mothers of toddlers can be continued, considering the impact felt by the target group.